Dionysian Plots from the Sculptural Frieze of the Theater of Nysa in the Context of the Era and the City - Korzun, Arina A. (Actual Problems of Theory and History of Art, 2021)
This article discusses the sculptural frieze from the theater of ancient Nysa (Caria) dated to the turn of the 2nd–3rd AD. The cycle of reliefs located on the podium of the scenae frons demonstrates the connection to the local myth of the rape of Persephone by Pluto and baby Dionysus sheltered by nymphs. These subjects could be placed in a row with the similar plots deriving from Dionysian narratives of the theaters of Asia Minor (Perge, Hierapolis, Side). The iconographical and semantic analysis reveals the connection of the narrative to the cultural environment of imperial era, particularly to the rhetoric movement of the second sophistry and imperial ideological programs, where the image of the governor and that of Dionysos are getting closer. The author also draws attention to distinctive features of sculptural frieze, discussing its composition and reconciliation of the plots. The analyses has been based on wide range of analogies deriving from plastic art and literature tradition.
Keywords: Nysa; baby Dionysus; Pluto; Persephone; triumph; theater’s frieze; narrative